1987
DOI: 10.1111/j.1472-8206.1987.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modafinil on Pancreatic Exocrine Secretion in Rats. A Comparison With Adrafinil and Related Drugs

Abstract: The effects of modafinil and adrafinil, 2 drugs that induce locomotor hyperactivity, and those of the parent compounds CRL 40467 and CRL 40385, were studied on the external pancreatic secretion of anaesthetized and conscious rats. In anaesthetized rats modafinil, adrafinil, and CRL 40385 antagonized the central vagal stimulation of protein output induced by 2-deoxy-D-glucose in the pancreatic juice. In conscious rats, modafinil and adrafinil inhibited the output of protein in the basal interdigestive pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The peak plasma concentration of adrafinil preceded peak behavioral and EEG response by about 1 h. This finding raises the possibility that the conversion of adrafinil to modafinil, the primary metabolite, is responsible for much, if not all, of the behavioral effects of adrafinil. This suggestion is supported in the few studies that have shown that the response to adrafinil directly compares to the response to modafinil (12). However, Ferner et al (24) have found the serum levels of adrafinil to be a better predictor of its effect on EEG response than the serum levels of modafinil; the subjects with the lowest serum concentrations of adrafinil showed the least pronounced effects.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The peak plasma concentration of adrafinil preceded peak behavioral and EEG response by about 1 h. This finding raises the possibility that the conversion of adrafinil to modafinil, the primary metabolite, is responsible for much, if not all, of the behavioral effects of adrafinil. This suggestion is supported in the few studies that have shown that the response to adrafinil directly compares to the response to modafinil (12). However, Ferner et al (24) have found the serum levels of adrafinil to be a better predictor of its effect on EEG response than the serum levels of modafinil; the subjects with the lowest serum concentrations of adrafinil showed the least pronounced effects.…”
Section: Introductionmentioning
confidence: 92%
“…The suggestion that adrafinil does not have peripheral adrenergic effects is also supported by evidence that α 1 -adrenergic receptor agonists do not block all of the effects of adrafinil. Chariot et al (12) found that adrafinil inhibited pancreatic secretions, and this was not prevented by treatment with prazosin. In fact, this effect of adrafinil on secretion is opposite to what is normally expected of an α-adrenergic agonist.…”
Section: The a 1 -Adrenergic Receptor Hypothesismentioning
confidence: 99%